O uso de um filme comercial no ensino de química: experiências dos estudantes do ensino médio - Rossato, Juliana Sbardelotto (2023)
Movies can be much more than just entertainment. In addition to art, form of expression and knowledge, they are also one of several didactic resources that have great didactic potential to be used in school. However, there are still common doubts about how to use them in classes, about its pedagogical relevance and even about its acceptance in the school environment. It is with this scenario in mind that this research has been conducted. We seek to understand the experiences of high school students about the use of films as a didactic-pedagogical resource in chemistry classes. With this, we identify how the use of film – particularly commercial ones – could contribute to student participation. To do so, we worked with a film in class, as part of a didactic sequence (SD) that developed the theme radioactivity with students from two first-year classes of the new high school, in the discipline of Chemistry. For the organization of SD, we adapted the stages of the three pedagogical moments proposed by Delizoicov, Angotti and Pernambuco. In the first of them, we briefly presented the subject we were going to work on and developed a questionnaire that allowed us to identify the students' previous knowledge about radioactivity and their experiences with films in classes. In the next stage, we held twelve classes on our topic, one of which we screened the film Radioactive, which had both the function of complementing the expository classes and of instigating the reflection of the students, who had to answer seven questions about the content of the classes with the support of the film. At the last moment, we systematically address the knowledge built by the student in this process. For this, we used a language script of questions that allowed us to observe how the students interpreted and related the cinematography with the school content. After this, we conducted interviews with the students, who were divided into ten groups of five individuals. In them, they were able to express themselves about what they thought of the experience with the use of films in the classroom. The dataset obtained was extensive. Thus, we chose to focus the analysis on those acquired in the interviews. For that, we used Discursive Textual Analysis (DTA). From it, twelve final categories emerged. The most important categories are: differentiated resource for teaching; inappropriate use of the film; ludic; clarifying instrument for understanding the content. They indicate and highlight the use of films as a valid didactic-pedagogical resource for the teaching process, insofar as it collaborated for the understanding of the worked content, by allowing the student to interact with elements addressed in class in a different way, a since films are clarifying instruments that instigate, motivate and involve students. Finally, we highlight the need and importance of teacher mediation so that this instrument can effectively contribute to science teaching.